Pemberdayaan Ibu Rumah Tangga di Desa Broto Melalui Skill Training: Pengolahan Limbah Ampas Kedelai Menjadi Kerupuk - Ulinnuha Nur Faizah; Amalya Rahil Nadivia; Maya Dwi Anggraini; Ulfi Hawin Mawadah (Amaluna: Jurnal Pengabdian Masyarakat, 2023)
Broto Village, located in the Slahung Subdistrict of Ponorogo Regency, faces suboptimal soybean residue management from tofu production, leading to environmental pollution. Employing the ABCD method with a Community Mapping approach, the Community Service Program (KPM) from IAIN Ponorogo identified the untapped social asset of the PKK (Family Welfare Empowerment) mothers. Empowering these mothers through training programs in transforming tofu residue into crackers is expected to mitigate environmental pollution. The program successfully recycled tofu residue into processed crackers, showcasing increased innovation among housewives in utilizing soybean residue for food production.